2012
DOI: 10.1007/s00217-012-1697-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of bacteriocins by Enterococcus spp. isolated from traditional, Iranian, raw milk cheeses, and detection of their encoding genes

Abstract: Strong bacteriocins, or bacteriocins with a wide range of activity against pathogens and spoilage microorganisms, are actively sought for use as natural food preservatives. This work reports the inhibitory activity of 96 enterococcal isolates from two Iranian, raw milk cheeses against Wve indicator organisms (including Listeria innocua). Forty-eight isolates inhibited at least one indicator in spot agar assays. Of these, 20 isolates corresponding to 15 diVerent strains were shown to produce bacteriocinlike sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…None of the evaluated strains showed PCR amplification fragments for enterocin L50A/B, bacteriocin 31, enterocin AS48, enterocin 1071A/1071B, and enterocin Q structural genes (Table 3). Previous studies showed that PCR detection of more than one bacteriocin encoding gene in the Enterococcus strains isolated from fermented foods is not unusual (6,11,15), as confirmed in this study. According to the classification scheme of Franz et al (18), enterocin A and enterocin P are grouped in class II.1 (pediocinlike bacteriocins), which has a very effective antilisterial activity, and enterocin B is grouped into class II.3 (linear nonpediocin-like bacteriocins).…”
Section: Detection Of Enterocin Structural Genessupporting
confidence: 89%
“…None of the evaluated strains showed PCR amplification fragments for enterocin L50A/B, bacteriocin 31, enterocin AS48, enterocin 1071A/1071B, and enterocin Q structural genes (Table 3). Previous studies showed that PCR detection of more than one bacteriocin encoding gene in the Enterococcus strains isolated from fermented foods is not unusual (6,11,15), as confirmed in this study. According to the classification scheme of Franz et al (18), enterocin A and enterocin P are grouped in class II.1 (pediocinlike bacteriocins), which has a very effective antilisterial activity, and enterocin B is grouped into class II.3 (linear nonpediocin-like bacteriocins).…”
Section: Detection Of Enterocin Structural Genessupporting
confidence: 89%
“…Moreover, they proved higher rates of incidence of these genes among isolates causing bacteremia and urinary tract infections (UTIs) compared to our analogous isolates: entlA Previous studies showed that PCR detection of more than one bacteriocin-encoding gene in the same Enterococcus spp. isolate from artisanal cheeses is not unusual (Edalatian et al 2012;Özden Tuncer et al 2013). In the present study, there was a higher dissemination rate of entA among E. faecium cheese isolates (93.3 %) compared to that among E. faecium isolated from traditional Iranian raw milk cheeses (72.7 %), whereas the entB and entP revealed lower frequency rates in our isolates than among Iranian ones (26.7 vs. 54.5 %) (Edalatian et al 2012).…”
Section: Discussionmentioning
confidence: 95%
“…isolate from artisanal cheeses is not unusual (Edalatian et al 2012;Özden Tuncer et al 2013). In the present study, there was a higher dissemination rate of entA among E. faecium cheese isolates (93.3 %) compared to that among E. faecium isolated from traditional Iranian raw milk cheeses (72.7 %), whereas the entB and entP revealed lower frequency rates in our isolates than among Iranian ones (26.7 vs. 54.5 %) (Edalatian et al 2012). Recently, Özden Tuncer et al (2013) isolated three bacteriocin-producer strains of E. faecium from artisanal Turkish tulum cheese and established the occurrence of eneterocin genes.…”
Section: Discussionmentioning
confidence: 95%
“…), lower percentage of E. faecalis strains in Lighvan cheese could be a positive point (Edalatian et al . ), as E. faecalis is clinically responsible for more than 80% of human enterococcal infections and is more invasive (Franz et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown high occurrence of enterococci in Lighvan cheese and their ability to produce antimicrobial substances such as enterocins (Edalatian et al . ).…”
Section: Introductionmentioning
confidence: 97%